Genotypes Identification of echinococcus granulosus isolated from iranian dogs and camels using three polymerase Chain reaction-based methods of cox1 gene - Mohsen Arbabi (International Archives of Health Sciences, 2021)
Aims: Hydatidosis is an important zoonotic disease that is caused by a tiny tapeworm, namely Echinococcus granulosus. In this study, three polymerase chain reaction (PCR)-based methods, including, high resolution melting (HRM) analysis, DNA sequencing, and PCR-restriction fragment length polymorphism (RFLP) have been used for genotype the identification of E. granulosus isolates from dogs and camels in Zarinshahr and Najafabad, Isfahan province, Iran. Materials and Methods: A total of 200 adult worms of 40 dogs and 51 samples of camel hydatid cysts were examined. Molecular characterization of isolates was performed using HRM assay, sequencing of DNA, and digestion Rsa1 pattern coding for the mitochondrial cox1 gene. For analysis of the HRM melting curve, we used the Tm within the range of 77.50°C–79.23°C. Results: HRM analysis revealed that 72.5%, 15%, and 12.5% dog's genotypes and 41.17%, 21.56%, and 35.29% camel genotypes were G1, G3, and G6, respectively. PCR-RFLP analysis, spare parts 310 bp and 138 bp of cox1 that shows the G1 genotype in all of the isolates. Sequence analysis as well as HRM assay was confirmed genotypes of G1, G3, and G6 in camels and dogs. Based on three methods of the cox1 gene the dominant genotype was G1. Conclusion: The PCR-RFLP only identified the G1 genotype, whereas the HRM analysis, as well as DNA sequencing, were detected three genotypes G1, G3, G6, therefore, these two methods have enough accuracy for the determination of genotypes of E. granulosus. This information leads to a better understanding of the biological characteristics of E. granulosus genotypes in Iran and shows the camel as a source of human hydatidosis.